The (d, 6Li) reaction in the f-p shell at Ed=27.25 MeV - Ceballos, Alberto E.; Erramuspe, Hugo; Ferrero, A. M. J.; Sametband, M. J.; Testoni, Juan; Bés, Daniel; Maqueda, E. E.; Perazzo, R. P. J.; Reich, S. L. (North Holland Publishing, 1974)
Fil: Ceballos, Alberto E. Comisión Nacional de Energía Atómica; Argentina